Clinico-Epidemiological Profile of Vitiligo Patients Receiving Narrowband Ultraviolet-B (NB-UVB) Treatment - Ramadhina, Anasya Putri; Setyaningrum, Trisniartami; Tjempakasari, Artaria; Damayanti (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Vitiligo is an idiopathic disease with a prevalence of 0.5-2% worldwide that causes the loss of melanocyte cells from parts of the body and is characterized by the appearance of well-defined white macules. The pathogenesis of vitiligo is suspected to originate from genetic, non-genetic, and autoimmune factors. Currently, Narrowband Ultraviolet-B (NB-UVB) is the first-line phototherapy treatment to treat vitiligo. Purpose: To evaluate the profile of vitiligo patients who were given phototherapy at the Dermatology and Venereology Outpatient Clinic, Dr. Soetomo General Academic Hospital for the period January-December 2019. Methods: This study used a retrospective descriptive research design with descriptive statistical methods. In this study, the medical records were evaluated by recording the patient's age, gender, occupation, history of illness, family history, and results of a physical examination. Result: This study obtained 31 samples that received phototherapy dominated by the age range of 17-25 years (29%) and male gender (55%), with a ratio of 1:0.82 to women. The majority work as others (68%). The most common trigger factor was emotional stress (29%). According to physical examination, the majority of patients had multiple lesions (81%), were not widely available (58%), and were of the generalized type (52%). Conclusion: It can be evaluated from the most data obtained: 17-25 years old (29%), male gender (55%), other occupations (68%), emotional stress triggers (29%), multiple lesions (81%), unavailable lesion area (58%), and generalized type (52%), describe the profile of vitiligo patients in Dr. Seotomo General Academic Hospital in 2019.